Case studies of the centre of pressure between hand and ball in off-spin bowling, analysed with a smart cricket ball - Fuss, F. K.; Doljin, B.; Ferdinands, R. E. D. (Procedia Engineering, 2016)
In off-spin bowling (finger-spin delivery with a sidespin, right-handed bowler), the ball rolls over the middle finger and rotates counterclockwise, as seen by the batsman. It is therefore expected that the torque imparted onto the ball is generated by the middle finger and the centre of pressure (COP) is also located close to the middle finger. The off-spin bowling action was recorded in five bowlers with a smart cricket ball and the COP was determined. In two bowlers, the COP was located at the middle finger and moved clockwise, i.e. against the sense of the ball, inherent to rolling motion. In one bowler, the COP was shifted slightly to the index finger, indicating a small contribution by the index to torque generation. Another bowler initiated the torque generation with the index finger, and then the COP moved from index to middle finger. The fifth bowler produced a rare case of braking i.e. deceleration of the ball at release, with the tip of the index finger, as seen in the location of the COP. In this case, the COP moved from the middle finger to the index. This preliminary study of off-spin bowling contributes to the understanding of torque generation, confirming that the primary torque generation is by the middle finger, a mechanism that could be more effective when combined with the torque generation by the index finger.